Pengaruh komposisi etanol sebagai zat aditif pada Sterculia Foetida Methil Ester terhadap pembakaran difusi - Dani Hari Tunggal Prasetiyo; Djoko Wahyudi (TURBO [Tulisan Riset Berbasis Online], 2022)
The amount of fossil energy reserves, especially fuel oil, which is dwindling, is the main focus for finding alternative energy sources. One of the most popular renewable energies today is biodiesel. Biodiesel can be obtained from free fatty acids from plants. One type of plant that can produce biodiesel as a raw material is kepuh (Sterculia foetida). The kepuh plant produces crude oil through fruit seeds which can be processed into biodiesel. However, biodiesel has a high viscosity value that affects the combustion reaction. Therefore we need an additive, namely ethanol to accelerate the combustion reaction. This study aims to determine the effect of the composition of ethanol in biodiesel on the characteristics of diffusion combustion. The research method used is the combustion diffusion test. The variables used in this study were the composition of biodiesel and ethanol. The composition of ethanol is 0%, 5%, 10%, 20%, 30%. The test results produce data that ethanol has an effect on the rate of diffusion of combustion and flame height. The combustion rate increases with the addition of ethanol and the flame height decreases with the addition of ethanol.